2005
DOI: 10.1128/jb.187.2.800-804.2005
|View full text |Cite
|
Sign up to set email alerts
|

SigB-Dependent In Vitro Transcription ofprfAand Some Newly Identified Genes ofListeria monocytogenesWhose Expression Is Affected by PrfA In Vivo

Abstract: Recent studies have identified several new genes inIn vitro transcription performed with promoters of some class III genes showed strict SigB-dependent but PrfAindependent transcription initiation. Transcription starting at the prfA promoter PprfA2 was also optimal with SigB-loaded RNA polymerase, suggesting a direct link between SigB-and PrfA-dependent gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 28 publications
6
66
0
Order By: Relevance
“…Accordingly, numerous PrfA-regulated virulence genes (Milohanic et al, 2003) showed upregulation after heat exposure, including plcA (lmo0201), encoding a phospholipase, inlA and inlB (lmo0433 and lmo0434), encoding Listeria-specific internalins, lmo2067, encoding a conjugated bile acid hydrolase, and lmo0596, encoding an unknown protein. However, Rauch et al (2005) have shown that PrfA has no direct influence on the transcription of lmo2067 and lmo0596. Significant down-regulation was found for the agr locus (lmo0048-lmo0051).…”
Section: Virulence-associated Genesmentioning
confidence: 99%
“…Accordingly, numerous PrfA-regulated virulence genes (Milohanic et al, 2003) showed upregulation after heat exposure, including plcA (lmo0201), encoding a phospholipase, inlA and inlB (lmo0433 and lmo0434), encoding Listeria-specific internalins, lmo2067, encoding a conjugated bile acid hydrolase, and lmo0596, encoding an unknown protein. However, Rauch et al (2005) have shown that PrfA has no direct influence on the transcription of lmo2067 and lmo0596. Significant down-regulation was found for the agr locus (lmo0048-lmo0051).…”
Section: Virulence-associated Genesmentioning
confidence: 99%
“…Furthermore in silico search revealed additional genes which contain in their upstream non-coding and hence probably regulatory regions sequences similar to PrfAbinding sites (PrfA-boxes) found in the well-established PrfA-dependent promoters of virulence genes of L. monocytogenes . However, neither in vivo nor in vitro transcription studies could demonstrate the direct involvement of PrfA in the transcription of these latter genes (Milohanic et al, 2003;Rauch et al, 2005). Thus, neither method has delivered reliable results concerning bona fide new PrfA- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these sequences were tested for PrfA-dependent promoter activity in the in vitro transcription assay (Rauch et al, 2005). None of these tested putative promoters responded to PrfA.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of this operon as a central mechanism in the sophisticated adaptive mechanisms to stress has been highlighted in a wide range of bacteria (Karlin et al, 2004;Satorhelyi, 2004). In L. monocytogenes, it is involved in resistance against alkali, oxidative, osmotic, heat, bile, and acid stress (Ferreira et al, 2004;Moorhead and Dykes, 2004;Sue et al, 2004;Giotis et al, 2008a) and is also important in virulence and the ability to invade host cells (Kim et al, 2005;Rauch et al, 2005;Garner et al, 2006). As might be expected of such an important regulon, sigB is itself subject to a complex regulatory system, and this study observed that AS induced significant upregulation of three genes (lmo0889, lmo0891, and lmo0892) that encode for proteins involved in the regulation of sigB.…”
Section: Adaptive Mechanismsmentioning
confidence: 99%